Specific Gestalt principles cannot explain (un)crowding - Choung, Oh-Hyeon; Rashal, Einat; Kunchulia, Marina; Herzog, Michael H. (Frontiers in Computer Science, 2023)
The standard physiological model has serious problems accounting for many aspects of vision, particularly when stimulus configurations become slightly more complex than the ones classically used, e.g., configurations of Gabors rather than only one or a few Gabors. For example, as shown in many publications, crowding cannot be explained with most models crafted in the spirit of the physiological approach. In crowding, a target is neighbored by flanking elements, which impair target discrimination. However, when more flankers are added, performance can improve for certain flanker configurations (uncrowding), which cannot be explained by classic models. As was shown, aspects of perceptual organization play a crucial role in uncrowding. For this reason, we tested here whether known principles of perceptual organization can explain crowding and uncrowding. The answer is negative. As shown with subjective tests, whereas grouping is indeed key in uncrowding, the four Gestalt principles examined here did not provide a clear explanation to this effect, as variability in performance was found between and within categories of configurations. We discuss the philosophical foundations of both the physiological and the classic Gestalt approaches and sketch a way to a happy marriage between the two.